Impact of ongoing intravenous thrombolysis until completion of endovascular treatment in large vessel occlusion stroke patients - Wischmann, Johannes; Pradhan, Cauchy; Zimmermann, Hanna; Keidel, Linus; Tiedt, Steffen; Dimitriadis, Konstantinos; Liebig, Thomas; Höglinger, Günter; Kellert, Lars (Frontiers in Neurology, 2023)
Background Recent studies implicated that ongoing intravenous thrombolysis (IVT) during endovascular treatment (ET) improves functional outcome in patients with stroke due to a large vessel occlusion (LVO). Here we investigate the effect of ongoing IVT until completion of ET on procedure duration, first pass thrombectomy rate and periprocedural complications. Methods We analyzed patients from the German Stroke Registry-Endovascular Treatment between June 2015 and December 2021. Primary outcomes were the modified Rankin Scale (mRS) after three months and a Thrombolysis In Cerebral Infarction (TICI)-score of 2b-3. Secondary parameters included ET-duration, first pass thrombectomy, and periprocedural complications. Results Out of 13.082 patients, 1639 met study criteria. N=317 (19.3%) had ongoing IVT until completion of ET, while IVT was finished in 1322 (80.7%). Ongoing IVT was associated with higher rates of mRS 0-2 (or back to baseline) after three months (odds ratio [OR] 1.53; 95% confidence interval [CI] 1.08-2.17). Furthermore, ongoing IVT predicted for higher rates of achieving a TICI-score of 2b-3 (OR 1.37; 95%CI 1.03-1.83) and first pass thrombectomy (OR 2.07; 95%CI 1.51-2.84), while reducing periinterventional complications (OR 0.64; 95%CI 0.44-0.94) and ET-duration by 24 minutes (β=-24.35; 95%CI -32.92-(-15.79)). Conclusion Our findings suggest that ongoing IVT until ET completion has a favorable impact on both clinical and angiographic outcomes, as well as on periprocedural conditions, regardless of overall time intervals. Therefore, rapid ET after IVT should be sought to take advantage of the additive effect of ongoing IVT during ET. Future studies should consider IVT timing in context of ET as a potential confounder treatment target.